(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: In the present era of rapid technological transformation, technical proficiency and adaptive capabilities have become crucial determinants of organizational success. Despite widespread access to training resources, many firms continue to struggle with persistent talent shortages and widening skill gaps. These gaps impede employee performance, reduce organizational efficiency, and ultimately affect economic progress. In current era of technological growth, individuals who possess proficient technical skills can easily elevate themselves to higher positions within organisations, enterprises, and society. It is a widely accepted fact that despite having access to numerous resources, many firms are still grappling with the fundamental challenges posed by the talent gap. The presence of skill gap issues not only hampers the performance of employees and companies, but also has a detrimental effect on the economic growth. Every organisation has the responsibility to detect skill gaps among personnel and implement effective ways to address these fundamental challenges. The primary objective of the study was to evaluate the discrepancy in skills and establish the correlation between skills and performance of the personnel employed in IT companies situated at Infopark cochin. A sample of 50 IT companies was chosen from the Infopark for the study. The necessary data for the analysis were gathered from the HR managers of the individual IT organisations. A well-designed questionnaire was used as the method of data collection. The study was done by analysing the employees' diverse skill sets, identifying skill gaps, assessing their influence on employee performance, and examining the strategies implemented by firms to address these issues. A strong correlation has been shown between the fundamental challenges of the skills gap and the performance of firms.